Pengaruh Implementasi Model Problem Based Learning (PBL) terhadap Kemampuan Berfikir Kritis IPA Siswa SMPN 1 Pakusari - Rizki Intan Rahmawati (ScienceEdu: Jurnal Pendidikan IPA, 2019)
The purpose of the research study is to analyze and find out what problems occur with respect to understanding and the ability to think critically of junior high school students against science subject with the application of the PBL model to better student activity. The method used is the collection of accurate information then analyzed and pretest-postest and fully understood and obtained a conclusion. Based on this preliminary study, it can be concluded that the application of the PBL model can have a positive influence on students thinking ability, which ultimately students can have a high curiosity about the phenomena that exist in the surrounding environment and also students are able to develop and develop the knowledge they already have. then with new knowledge added to the amplifier. Keyword: Problems Based Learning (PBL); Critical Thinking Ability; Environment